Ответ:
Пошаговое объяснение:
первое уравнение:
-7-5(7-4х)=19
-7-35+20х=19
-42+20х=19
20х=19+42
20х=61
х=61/20
второе уравнение:
-4(1/7х+3)=-13
1/7х+3=-13/-4
1/7х+3=13/4
1/7х=13/4-3
1/7х=13/4-12/4
1/7х=13-12/4
1/7х=1/4
х=1/4•7
х=7/4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
первое уравнение:
-7-5(7-4х)=19
-7-35+20х=19
-42+20х=19
20х=19+42
20х=61
х=61/20
второе уравнение:
-4(1/7х+3)=-13
1/7х+3=-13/-4
1/7х+3=13/4
1/7х=13/4-3
1/7х=13/4-12/4
1/7х=13-12/4
1/7х=1/4
х=1/4•7
х=7/4